KAJIAN SIFAT MAGNETIK SEDIMEN TELUK KATURAI PULAU SIBERUT KEPULAUAN MENTAWAI - HARIS, VENNY; Rifai, Hamdi (Sainstek : Jurnal Sains dan Teknologi, 2010)
This study aimed to examine the magnetic properties of sediments from Teluk Katurai Siberut island Mentawai islands. The study on sediment samples from Teluk Katurai had been carried out by using three methods, i.e., measurements of AMS (Anisotropy of Magnetic Susceptibility) to determine the anisotropy shape of magnetic susceptibility, IRM (Isothermal Remanent Magnetization) to identify the their magnetic minerals contains based on the saturation curve, and AAS (Anisotropy of Anhysteretic Susceptibility) that produce anhisteritik susceptibility. From the stereonet plot and other anisotropy parameters were obtained that ellipsoid susceptibility form is oblate. It was also obtained that the type of magnetic mineral is magnetite based on magnetic saturation curves. Meanwhile the identification of grain size distribution was obtained by plotting the value of AMS versus AAS. The plots showed the magnetic grains of sediment was approximately 0.2 µm to 0.1µm.Key words: magnetic susceptibility, anisotropy, anhisteritic susceptibility